Impact of body mass index on the clinical outcomes of patients with HER2-positive metastatic breast cancer. (February 2018) - Martel, Samuel; Poletto, Elena; Ferreira, Arlindo R.; Lambertini, Matteo; Sottotetti, Federico; Bertolini, Ilaria; Montemurro, Filippo; Bernardo, Antonio; Risi, Emanuela; Zanardi, Elisa; Ziliani, Serena; Mura, Silvia; et al.
Abstract: Background: Overweight and obesity are associated with an increased risk of developing many types of cancer, including breast cancer. Moreover, increased body mass index (BMI) seems to be associated with a worse prognosis in patients with HER2-positive early breast cancer. However, little is known about the impact of BMI on the clinical outcomes of HER2-positive metastatic breast cancer (MBC). Methods: This was a multicenter retrospective cohort study including 329 consecutive patients with HER2-positive MBC treated with first-line trastuzumab-based regimens. BMI at the time of MBC diagnosis was collected. World Health Organization BMI categories were used: underweight <18.5, normal 18.5–24.9 Kg/m 2, overweight 25–29.9 Kg/m 2, and obese ≥30 Kg/m 2 . The analyses were conducted using two categories: BMI < 25.0 (normal/underweight) and BMI ≥ 25 (overweight/obese). Progression-free survival (PFS) and overall survival (OS) rates were estimated using Kaplan-Meier method. Univariate and multivariate survival analyses were performed using the Cox's proportional hazards model. Disease response to therapy was analyzed using univariate and multivariate logistic regression. Results: Overall, 176 (53.5%) patients were normal/underweight and 153 (46.5%) overweight/obese. Median PFS was 14.8 months in BMI < 25 group and 15.7 months in BMI ≥ 25 group (adjusted-HR 0.88; 95% CI 0.66–1.17; p = 0.387). Median OS was 58.6 months in BMI < 25 group and 52.6 in BMI ≥ 25 group (adjusted-HR 0.88; 95% CI 0.59–1.31; p = 0.525). Overall response rate was 71.7% and 65.9% (p = 0.296) and clinical benefit rate was 82.1% and 83.3% (p = 0.781) in BMI < 25 and BMI ≥ 25 groups, respectively. Conclusions: BMI does not seem to be associated with clinical outcomes in HER2-positive MBC patients. Highlights: Body mass index (BMI) is a weight-for-height ratio used to assess a person's relative body fatness. Limited data are available on the impact of obesity in HER2-positive metastatic breast cancer (MBC). No difference in progression-free survival to first-line trastuzumab was observed according to BMI. There was no overall survival difference between normal/underweight and overweight/obese patients.